Anti-herpetic activity exopolysaccharides produced by different species of lactic acid bacteria - Naumenko, Krystyna; L, Biliavska; Y, Pankivska; O, Povnitsa; O, Vasyliuk; I, Garmasheva; S., Zagorodnya (JOURNAL OF ADVANCES IN BIOLOGY, 2019)
In the present work, it was shown that, in non-toxic concentrations, all EPSs which were isolated from lactic acid bacteria have significant anti-HSV-1 activity affecting various stages of the virus reproduction. It was demonstrated that the use of ESPs leads to the normalization of the life cycle of cells infected with the herpes simplex virus to the level of uninfected cells. It was found that EPS 26a produced by Lactobacillus sp. possesses multiple antiviral effects as it exhibits virucidal activity, blocks adsorption, penetration of the virus into cells and the release of viruses, and reduces the infectious titer of herpes simplex virus by 97-99%, indicating its considerable anti-herpetic activity.